Strong and fragile topological Dirac semimetals with higher-order Fermi arcs - Benjamin J. Wieder (Nature Portfolio, 2020)
The existence of a topological bulk-boundary correspondence for Dirac semimetals has remained an open question. Here, Wieder et al. predict one-dimensional hinge states originating from bulk three-dimensional Dirac points in solid-state Dirac semimetals, revealing condensed matter Dirac fermions to be higher-order topological.